2021
DOI: 10.1186/s12877-020-01948-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild cognitive impairment in community-dwelling Chinese populations aged over 55 years: a meta-analysis and systematic review

Abstract: Background Mild cognitive impairment (MCI) is an intermediate phase between normal cognitive ageing and overt dementia, with amnesic MCI (aMCI) being the dominant subtype. This study aims to synthesise the prevalence results of MCI and aMCI in community-dwelling populations in China through a meta-analysis and systematic review. Methods The study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) protocol. Engl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 95 publications
4
59
0
2
Order By: Relevance
“…More female patients were diagnosed with MCI at 58.3% consistent with findings in other population [2]. Other studies have also shown how the female sex tend to exhibit lower ADAS-Cog scores when followed up for over 8-10 years, highlighting the influence of female sex as a risk for progression [12,13].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…More female patients were diagnosed with MCI at 58.3% consistent with findings in other population [2]. Other studies have also shown how the female sex tend to exhibit lower ADAS-Cog scores when followed up for over 8-10 years, highlighting the influence of female sex as a risk for progression [12,13].…”
Section: Discussionsupporting
confidence: 85%
“…The patients seen in the Memory Center actively seek consult due to subjective cognitive concerns from the patients themselves, their families, or their referring doctors; thus, the diagnosis and prevalence of MCI are higher than a community setting. Literature reported that MCI is more frequent among patients from rural communities [2], but the Memory Center is a specialty referral unit and caters to patients from both rural and urban areas. This should be highlighted and considered when comparing our study results with those researches among community-dwelling individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amnestic mild cognitive impairment (aMCI) is a dominant subtype of MCI in which memory loss is the predominant symptom, accounting for 66.5% of all MCI cases [1]. People with aMCI are more likely than other subtypes to develop dementia, which is considered a precursor to Alzheimer's disease (AD) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%